COMPOSITION OF A DENSE SEMICLASSICAL PARTIALLY IONIZED CARBON PLASMA - Gabdullin, M. T.; Ramazanov, T. S.; Dzhumagulova, K. N.; Redmer, R. (Recent Contributions to Physics, 2009)
The composition of a dense semiclassical partially ionized carbon plasma were calculated on the basis of modified Saha equation. The lowering of ionization potentials was derived by the effective potentials, witch take into account diffraction effects on the small distance and screening effects on the long distance.